The virucidal properties of silver ion-exchange resins and metal-based nanoparticles and their potential use in water purification - Scott, Greg Michael (Kansas State University, 2010)
Contamination of water with various disease causing agents such as bacteria and viruses leads to 4 billion cases of diarrheal disease and 1.8 million deaths per year worldwide. The World Health Organization estimates that 94% of these cases can be prevented by increasing the availability of clean and safe water to those at risk. They also claim that 1.1 billion individuals worldwide do not have access to clean water sources, and suggest the best way to improve this situation is to increase household water treatment and safe storage (HWTS). HWTS can dramatically improve water quality, leading to a significant reduction in diarrheal disease. Being able to produce a small and inexpensive device that can be used in a household to improve water quality will significantly aid in preventing diarrheal disease. Water purification systems have been manufactured in the past in order to turn potentially disease causing water into safe drinking water. The metal iodine has been used in some of these systems. However, iodine is known to leach off and become part of the drinking water, which can lead to non-infectious diseases such as hyperthyroidism. This project shows how the development of new water purification systems utilizing silver and other heavy metal nanoparticles may be used to help purify water and have the potential to prevent diarrheal disease. Various heavy metals, including silver nitrate, magnesium oxide, brominated magnesium oxide and titanium-silicon-manganese dioxide nanoparticles, are used in conjunction with ion-exchange resins to develop a biocidal column to sanitize water. A model virus from each of the following families is used: Reoviridae (rotavirus), Picornaviridae (enterovirus), and Caliciviridae (calicivirus). This research shows not only that some of these metals can be used to purify water by inactivating viruses, but also shows the mechanism of viral inactivation. This includes protein denaturation and destruction of viral RNA.
Keywords: virus; silver; nanoparticle; water; Biology, Microbiology (0410)